FINDING WAYS OF RECYCLING DUST OF ARC STEEL FURNACES AT THE BELARUSIAN METALLURGIC PLANT - A. V. Demin; A. I. Rozhkov; О. М. Grudnickij; V. V. Nikolaev; A. V. Feklistov (Литьë и металлургия)
The first part examines the theoretical possibility of recycling dust of arc steel furnaces. The different modes of dust disposal depending on the task of recycling are discussed: recycling at minimal cost; recycling with a maximum extraction of iron; recycling with maximum extraction of zinc. The results of laboratory studies providing information on the technical feasibility of recycling dust formed at the Belarusian metallurgic plant are provided.